2020
DOI: 10.3348/kjr.2019.0798
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Volume Reduction Ratio Predicts Regrowth and Time to Regrowth in Thyroid Nodules Submitted to Laser Ablation: A 5-Year Follow-Up Retrospective Study

Abstract: Objective: Laser ablation is a therapeutic modality used to reduce the volume of large benign thyroid nodules. Unsatisfactory reduction and regrowth are observed in some treated nodules. The aim of the study was to evaluate the long-term outcomes of laser treatment for solid nodules during a 5-year follow-up period, the regrowth rate, and the predictive risk factors of nodule regrowth. Materials and Methods: We retrospectively evaluated patients with benign, solid, cold thyroid nodules who underwent laser abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 36 publications
2
32
1
4
Order By: Relevance
“…As alternatives to surgery, the long-term efficacy of thermal ablation techniques has attracted research attention. Sim et al [20] found that the nodule regrowth began at 12 months and tended to be prominent after 2 years of follow-up with an incidence of 4.1-37.5% [19][20][21][22][23][24]. Recently, a multicenter study found that regrowth occurred in 20% of patients who were followed for 5 years after a single session of RFA [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As alternatives to surgery, the long-term efficacy of thermal ablation techniques has attracted research attention. Sim et al [20] found that the nodule regrowth began at 12 months and tended to be prominent after 2 years of follow-up with an incidence of 4.1-37.5% [19][20][21][22][23][24]. Recently, a multicenter study found that regrowth occurred in 20% of patients who were followed for 5 years after a single session of RFA [25].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the sample size was relatively small, partially in the regrowth group, resulting in a small number for events per variable in logistic regression analysis. However, the overall incidence of nodule regrowth was only 4.1 to 37.5% [19][20][21][22][23][24][25]. It was very difficult to collect enough data for events per variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been similar studies previously. In a study by Negro et al who retrospectively analyzed the results of 5-year follow-up after laser ablation, a 12-month VRR < 50.0% is a predictive risk factor for regrowth and correlates with the time to regrowth [5]. In addition, Sim and Park observed that the IAR is linearly correlated with the 12month VRR, and if IAR < 70%, it can be used for the early prediction of regrowth [6,7].…”
Section: Rvr As An Early Sign Of Regrowth: Comparison With Iar and 12mentioning
confidence: 99%
“…Dear Editor, I read with great interest the report by Negro et al (1) titled "Twelve-Month Volume Reduction Ratio Predicts Regrowth and Time to Regrowth in Thyroid Nodules Submitted to Laser Ablation: A 5-Year Follow-Up Retrospective Study." This study presented long-term follow-up results of single session laser ablation (LA) for symptomatic benign thyroid nodules.…”
mentioning
confidence: 99%